Discurso direto e hipossegmentações na aquisição da escrita - Ticianel, Giordana França (2016)
The objective of this research was to investigate possible relations existing between the direct speech and the existence of hyposegmentations in textual production from children of the Elementary School. To do so, we examined the functioning of such occurrences based on the enunciative position in which they were produced: in the direct speech itself (DS) and in the moments classified as other contexts (OC). More specifically, we aimed the investigation, both quantitatively and qualitatively, about the existence of differences between the hyposegmentations observed in DS and OC. The material investigated was constituted by 3113 textual productions made by children from the old four first grades of Elementary School from municipal schools. The research relies on the writing conception proposed by Corrêa (1997, 2004) - which postulates it as constitutively heterogeneous - such as it understands, enlightened by the studies of Capristano (2007a, 2007b, 2010), Chacon (2004, 2009, 2013), Tenani (2008, 2010, 2011), Capristano e Ticianel (2014), and others, that the hyposegmentations are indications of the writer's movement in oral and literacy practices. In the quantitative examination of the hyposegmentations, we observed that, in all the grades investigated, there were more words involved in hyposegmentation, as well as occurrences of hyposegmentarions, in OC than in DS. Furthermore, we observed that the hyposegmentations, throughout the four grades, were similarly distributed in the two enunciative positions. These results allowed us to postulate that, quantitatively, there was no relation between the presence of DS and the emergence of hyposegmentations. In the qualitative examination of the hyposegmentations, we investigated if they were associated to prosodic limits as proposed by Nespor and Vogel (1986) and, if so, to which one: clitic group (C), phonological phrase (Φ), intonational phrase (I) and utterance (U). Among the main results found in the qualitative analysis, we determined, firstly, that the majority of hyposegmentations that do not emerge as effect of the influence of prosodic limits were placed in OC. Secondly, from those which emerged as effect of the influenced of prosodic limits, the majority of the ones which were associated to C, Φ and I limits presented similar functioning in both DS and OC. Lastly, we could observe that the hyposegmentations that were associated to U limits were directly related to the enunciative position from which they emerged, because there was a considerably superior occurrences in DS. This result is connected to the fact that the U has its borders related to prosodic and syntactic factors, which can also be linked to the limits of DS excerpts. We could conclude, from all the investigation, that a multiplicity of factors enables the emergence of hyposegmentations. However, for some of them, certain factors were more relevant, for example, the enunciative positions in which the writers enunciated. These positions may be, then, sometimes, determinant for the emergence of certain types of non-conventional segmentations.